CREATION OF CLOSED PRODUCTION CYCLES IN AGRICULTURAL ENTERPRISES: “FROM FIELD TO FINISHED PRODUCT” - Vovk, Bohdan (SWorld-Ger Conference proceedings, 2025)
The paper examines the concept of closed production cycles in agribusiness as a key instrument for transitioning from a linear to a circular economic model. It analyzes the managerial, technological, and economic aspects of implementing the “from field to